PERAN TUTOR DALAM MENINGKATKAN MOTIVASI BELAJAR WARGA BELAJAR KESETARAAN PAKET A DI PKBM MEKAR ASRI - Annisa, Fahira Nur; Triyanti, Ainurrochma; Sari, Putri Puspita; Dwi.A, Imelda; Ferdiansyah, M. Arif; Naila, Ika Derin; Susilo, Heryanto; Qodriyanti, Tri Ulya (JPUS: Jurnal Pendidikan Untuk Semua, 2024)
Learning motivation is a crucial element in the success of education, especially in the context of non-formal education such as the equivalency program Paket A. This study aims to explore the contribution of tutors in enhancing the learning enthusiasm of learners at PKBM Mekar Asri Surabaya. The research employed a descriptive qualitative method with data collection techniques including observation, interviews, and documentation involving the head of PKBM, two tutors, parents, and three learners. The findings reveal that tutors function not only as instructors but also as facilitators, motivators, and mentors who can create a pleasant, flexible, and contextual learning environment. Tutors apply a personal approach, provide recognition, and utilize both face-to-face and independent learning methods tailored to the learners’ needs. Furthermore, the role of parents is also proven to be important in shaping learners’ external motivation through moral support and a supportive learning environment. This study emphasizes that collaboration between tutors and parents is essential in creating an effective and sustainable learning process that can enhance learners’ motivation and improve their quality of life through non-formal education.